DOKTRIN PESANTREN TERHADAP PEREMPUAN (Kajian Terhadap Kitab-kitab dan Realitas Perempuan di Dalam Pesantren) - abdullah, gazali; Akib, Mohammad Nawir (FAI Unismuh Palu, 2019)
ABSTRAKThis research found that Pesantren tend to use preventive treatments in responding to women's problems, by trying to maintain traditions and books that have been applied in pesantren since a long time ago. This study also agrees with Masdar Farid Mas’udi (2000), Nasaruddin Umar (2014), and Zaitunah Subhan (2015). Stating that an Islamic classic book that have been left by the previous muslim scholars way too much, but so far, we have focused on the classic books that seems irrelevant to the reality of community construction, especially on women's issues. Being agree and obey to certain books by denying reality and other arguments can cause a rigid construction of thought. Thus, someone’s understanding can have an impact on destructive thinking in seeing the Islamic classic book, especially on women's issues. This research seems contradictory to Yunahar Ilyas (2015) stating that muslim scholars are not entirely in one thought to the human creation concept, the main point of disagreement is in the nafs wahidah and minha sentences in surah an-Nisa verse number 1, as well as differences in assessing the quality of hadith about the creation of Eve from the ribs. Yunahar is more inclined to the argument states that the creation of women is from ribs. While Khuzaemah T. Yanggo (2010) stated that a women must not deny their domestic obligations, even if they choose to work outside their home like what man do. According to Khuzaemah, this is an Islamic Sharia provision which every woman muslim must obey it. This research is a library research. The approach used in is the socio-historical approach. Primary data of this study are the main books that are used as references by pesantren, including Riyadu al-Salihin, Subulus Salam, Fath al-Qarib, Fath al-Baari, Fath al-Mu’in etc. Whereas the secondary sources are the books of hadith and fiqh, sharh hadith and sirah al-Nabawiyah especially the books relating to the women issues. Keywords: Pesantren, Women, Doctrine